THE CUSTOMER RELATIONSHIP MANAGEMENT MODEL AT THE HOSPITALITY ENTERPRISE (INNOVATIVE ECONOMY, 2023)
Nahara M.B. THE CUSTOMER RELATIONSHIP MANAGEMENT MODEL AT THE HOSPITALITY ENTERPRISEPurpose. The purpose of the article is to systematize the approaches to defining the concept of “Customer Relationship Management” and to develop the CRM-model for the hospitality enterprise.Methodology of research. The theoretical and methodological basis of the article are the fundamental researches of modern economic theory, scientific works of leading domestic and foreign scientists concerning CRM in the hospitality sector. The following methods are used in the process of writing the article in order to achieve the goal: theoretical generalization – to highlight common features of the concept of “Customer Relationship Management; monographic and systematic analysis – to substantiate the essence of the CRM-system; abstract and logical – to develop the CRM-model for the hospitality enterprise; graphic - for visual presentation of the research results.Findings. It is substantiated that CRM in the hospitality industry is an integrated approach to identifying, attracting and retaining consumers of hospitality services and products. It is determined that the main components of the CRM-system are: customer knowledge management; marketing policy of service promotion; sales system; value creation for the customer; pricing policy; information support. It is found that the CRM system includes a set of principles, methods and tools that are logically interconnected and integrated into a corporate information environment in order to increase sales, improve marketing and customer service, and to optimize enterprise business processes.Originality. The CRM-model for the hospitality enterprise is developed. The model makes it possible to convert employee knowledge and information about customer needs into new key competencies of the enterprise. It creates opportunities for sustainable economic growth, increases enterprise competitiveness and customer loyalty.Practical value. The main directions of the article make it possible to increase the relevance of management decisions in the process the CRM-model implementing and improving at the hospitality enterprise.Key words: Customer Relationship Management, CRM-model, hospitality enterprise, loyalty, development, competitiveness.
Keywords: Customer Relationship Management; CRM-model; hospitality enterprise; loyalty; development; competitiveness